Perturbing the consistency of auditory feedback in speech - Nault, Daniel R.; Mitsuya, Takashi; Purcell, David W.; Munhall, Kevin G. (Frontiers in Human Neuroscience, 2022)
Sensory information, including auditory feedback, is used by talkers to maintain fluent speech articulation. Current models of speech motor control posit that speakers continually adjust their motor commands based on discrepancies between the sensory predictions made by a forward model and the sensory consequences of their speech movements. Here, in two within-subject design experiments, we used a real-time formant manipulation system to explore how reliant speech articulation is on the accuracy or predictability of auditory feedback information. This involved introducing random formant perturbations during vowel production that varied systematically in their spatial location in formant space (Experiment 1) and temporal consistency (Experiment 2). Our results indicate that, on average, speakers’ responses to auditory feedback manipulations varied based on the relevance and degree of the error that was introduced in the various feedback conditions. In Experiment 1, speakers’ average production was not reliably influenced by random perturbations that were introduced every utterance to the first (F1) and second (F2) formants in various locations of formant space that had an overall average of 0 Hz. However, when perturbations were applied that had a mean of +100 Hz in F1 and −125 Hz in F2, speakers demonstrated reliable compensatory responses that reflected the average magnitude of the applied perturbations. In Experiment 2, speakers did not significantly compensate for perturbations of varying magnitudes that were held constant for one and three trials at a time. Speakers’ average productions did, however, significantly deviate from a control condition when perturbations were held constant for six trials. Within the context of these conditions, our findings provide evidence that the control of speech movements is, at least in part, dependent upon the reliability and stability of the sensory information that it receives over time.